(untitled) (Ahkam: Jurnal Hukum Islam, 2024)
This article explains the views of KH Ahmad Bahauddin Nursalim on “the khilafah” as prescribed in Surat An-Nur verse 55. The method used in this research is a qualitative research with a content analysis approach and using al-Ghazali’s philosophy for analysing. This research analyzes the explanation of KH Ahmad Bahauddin Nursalim about the khilafah as presented in the video containing his study of the Book of Tafsir Jalalain. It was found in You Tube account entitled “Ngaji Gus Baha Jogja” with the theme “Makna Khilafah” in a video that lasts 1 hour, 25 minutes, and 35 seconds. This research found that KH Ahmad Bahauddin Nursalim believes that the promise of Allah about the realization of Islamic khilafah for the believers is likely to be realized in the future, not today. Hence, he advised those who had knowledge to be patient and not to fail in interpreting the verses of the Qur’an. Khilafah, for the time being, cannot be applied in Indonesia because of its highly multi-religious and multicultural demographic conditions. If the khilafah is applied, there is potential chaos that threatens the sovereignty of the country. The view of KH Ahmad Bahauddin Nursalim is a moderate one in the very harsh rejection of khilafah and not out of the original meaning of the text of Surat an-Nur verse 55. If reviewed from the theory of division categories of maslahat according to al-Ghazali in understanding the text about this khilafah, the view of KH Ahmad Bahauddin Nursalim that “khilafah is irrelevant for today’s time” can be categorized as maslahat dzaruriyat; otherwise, then there will raise chaos. For further research, the author suggests that the view of Khilafah by KH Ahmad Bahauddin Nursalim can be compared with the views of other moderate scholars.